Investigating Motivations of Learning Languages Other Than English: A Case of Learners of Japanese in Thailand - Jenjira Jitpaiboon; Atichat Rungswang; Yuki Miyamoto (My University, 2024)
Current theories about learning a second language might not fully explain why people want to learn languages other than English (LOTE) in the context of globalization and multilingualism. This study adopted and adjusted Huang’s (2021) motivational dimensions for LOTE learners, specifically focusing on those who learn LOTE as a third language (L3), as is common in Thailand. It aimed to explore the motivations of 167 Thai students in higher education when choosing to study Japanese, using a questionnaire and a focus group. The findings indicate that Culture/Community Interest and Instrumentality-Promotion significantly influence motivation. On the other hand, Instrumentality-Prevention and Intended Learning Effort are closely related and exhibit the least influence. The findings also showed that students’ motivations change depending on their year of study. Third- and fourth-year students valued practical benefits the most, while second-year students were more interested in the culture and community of the target language. In addition, the research also examined students’ perceptions of multilingual learning. This research helps educators, linguists, and policymakers understand why students want to study Japanese and to create effective teaching strategies tailored to students’ interests.
Keywords: EFL/ESL Teaching and Learning